Aspect of Legal Protection on Buying Transactions of Thrift Shop Products Sharia Economic Law Perspective - Rahmatul Huda; Miftah Sya'bana; Umi Hani; Abdul Hadi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
The process of human life, one of which affects the human lifestyle. This lifestyle can lead to consumptive behavior because of the desire to keep up with the times. Calculated from year to year, there has been an increase in the production of clothes or garments that have doubled from before. The buying and selling of used clothes have been around for a long time, but lately during the pandemic these activities are busy in the community. Currently, the term imported used clothing is more familiar with thrift clothing. This thrift activity has even penetrated social media and online shopping platforms. Whereas the prohibition of imported used clothes is contained in Law Number 7 of 2014 concerning Trade which has been explicitly stated in Article 47 by stating that "importers are obliged to import goods in new conditions". Another prohibition on the sale and purchase of imported used clothes (thrift) can also be found in Article 8 paragraph (2) of Law Number 8 of 1999 concerning Consumer Protection (UUPK). The purpose of this study is to determine aspects of legal protection in buying and selling transactions of thrift shop products and to determine the analysis of sharia economic law on aspects of legal protection in buying and selling transactions of thrift shop products. This type of research is normative legal research with a conceptual approach. The results of this study indicate that aspects of legal protection in the sale and purchase of thrift shop